Case Report: Anlotinib Reverses Nivolumab Resistance in Advanced Primary Pulmonary Lymphoepithelioma-Like Carcinoma With FGFR3 Gene Amplification - Liu, Yanyang; Long, Lang; Liu, Jiewei; Zhu, Lingling; Luo, Feng (Frontiers in Oncology, 2021)
Background: Primary pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare type of non-small cell lung cancer (NSCLC). Currently，the anti-programmed death-1 (PD-1) / programmed death ligand-1 (PD-L1) has become an important treatment for NSCLC. Anti-human PD-1 monoclonal antibody such as nivolumab significantly prolongs the survival time of patients with advanced lung adenocarcinoma and lung squamous cell carcinoma. However, there are few reports on the therapeutic effect, drug resistance mechanism and strategies to overcome resistance of anti-PD-1/PD-L1 treatment in advanced pulmonary LELC. We report a patient with advanced pulmonary LELC harboring FGFR3 gene amplification showed a resistance to nivolumab. After treatment with anlotonib, a multi-targeted small molecule tyrosine kinase inhibitor (TKI), the patient resistance to nivolumab was reversed. She achieved a long-term disease remission by the combination of anlotinib and nivoluamb treatment. Case Presentation: A 68-year-old woman was diagnosed with stage IVA pulmonary LELC. After multiple-line chemotherapy, her diseaes was progressed. Since the PD-L1 expression rate of the patient was 90%, she was administrated with nivolumab. But the therapeutic effect of nivolumab was not ideal, the disease continued to progress, and a new cervical lymph node metastase appeared. The FGFR3 gene amplification was detected in the lymph node metastase. Baesd on this gene abnormal, we added the anlotinib into the treatment. After two cycles of anlotinib and nivolumab, the metastatic focus of the patient was significantly reduced. The patient continued to receive this combined treatment and achieved remission for more than 15 months. Conclusion: Pulmonary LELC with FGFR3 gene amplification may not respond well to nivolumab monotherapy. The combination of anlotinib and nivolumab can reverse the resistance to nivolumab in pulmonary LELC with FGFR3 gene amplification.